Structure–property correlations and magnetoelectric response of lead-free BNT–BCTS/CZFMO composite ceramics - Kornphom, Chittakorn; Sonchaopri, Nutkamon; Yimsabai, Sununta; Yotthuan, Surirat; Jantaratana, Pongsakorn; Pinitsoontorn, Supree; Vittayakorn, Naratip; Pankaew, Aphiwat; Bongkarn, Theerachai (My University, 2026)
Lead-free multiferroic composite ceramics have garnered increasing attention as an eco-friendly alternative for magnetoelectric (ME) devices. In this work, (100-x) [0.93(Bi0.5Na0.5TiO3) 0.07(Ba0.945Ca0.055Ti0.91Sn0.09O3)]/xCo0.6Zn0.4Fe1.7Mn0.3O4 composite ceramics, abbreviated as (100-x) BNT-BCTS/xCZFMO were synthesized via a solid-state combustion route. Analysis of XRD data using the Rietveld method confirmed the coexistence of rhombohedral and tetragonal perovskite (BNT–BCTS) phases and a cubic spinel (CZFMO) phase without additional impurity phases. The 0–3 connectivity was verified using SEM/EDS, PFM, and MFM measurements, confirming discrete CZFMO magnetic grains are embedded within a continuous BNT–BCTS piezoelectric matrix. Williamson–Hall (W–H) analysis, treated as a semi-quantitative approach due to fitting limitations in the multiphase composite system, suggested a composition-dependent microstrain trend. The reduced microstrain at intermediate CZFMO contents was consistent with enhanced crystallite growth, improved densification, and the maximum magnetoelectric response. The composition with x = 20 exhibits the highest relative density (~ 98.14%), the highest saturation magnetization (Ms = 6.55 emu/g), and the maximum magnetoelectric coefficient (αME = 7.92 mV cm−1 Oe−1), showing higher ME coefficients than many previously reported lead-free composites. This work demonstrates the potential of BNT–BCTS/CZFMO composites for multifunctional electronic devices, including magnetic sensors, energy harvesters, and magnetoelectric transducers.